Design and analysis of tail boom section for a designated piston powered 4-seater helicopter [electronic resource] - 184037 Mohd. Firdaus Mohd. Zin (2008)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Aeronautik)) - Universiti Teknologi Malaysia, 2008